Políticas públicas de Economia Solidária e a SENAES: um balanço preliminar (2003-2006) - Goulart, Jefferson Oliveira [UNESP]; Marin, Thais Rodrigues (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2012)
This paper focuses on the process of institutionalization of public policies of Solidarity Economy in the federal government during President Lula’s first term (2003-2006). During this period, the authors analyze in particular the creation and operation of the National Secretariat for Solidarity Economy (SENAES) – a structure established under the Ministry of Labor in order to implement social inclusion policies designed to generate jobs and income. This approach allows the formulation of hypotheses about the institutional context of SENAES, its scope, limits and challenges.

O presente trabalho focaliza o processo de institucionalização das políticas públicas de Economia Solidária no governo federal durante o primeiro mandato do presidente Lula (2003-2006). Neste período, são analisadas especialmente a criação e a atuação da Secretaria Nacional de Economia Solidária (SENAES) – estrutura fundada no âmbito do Ministério do Trabalho e Emprego com o propósito de implantar políticas de inclusão social com geração de trabalho e renda. Essa abordagem permite a formulação de hipóteses sobre a inserção institucional da SENAES, seus alcances, limites e desafios.
Public policies of Solidarity Economy and SENAES: a preliminary assessment (2003-2006)
Keywords: Solidarity Economy; SENAES; Public policies; Economia Solidária; SENAES; Políticas públicas